The Catholic Church and the Northern Ireland Troubles, 1968-1998 - Scull, Margaret M. (Oxford University Press, 2019)
This work provides an indispensable study of the role played by the Catholic Church during one of the most tumultuous periods of British and Irish history - the Northern Ireland Troubles - showing evidence which offers a radical new perspective on religious institutions as conflict mediators in the twentieth century.